Increased terahertz emission from SI-GaAs deposited with sub-wavelength spacing metal line array - Faustino, Maria Angela B. (Animo Repository, 2015)
Increased terahertz (THz) emission of surface modified semi-insulating gallium arsenide (SI-GaAs) is reported. A metal line array with sub-wavelength spacing was fabricated via e-beam deposition and THz measurements were done in the transmission excitation geometry. Results show an order of magnitude THz broadband emission enhancement. Pump-power dependent measurements were also utilized which shows a nonlinear dependence with the THz integrated intensity. This broadband enhancement is currently attributed to super transmission owing to a non-linear optical effect that may be related to surface plasmon resonance.